Synthesis of different inorganic anions intercalated layered double hydroxides and ion exchange characteristics - XIE Zhi-hui; SHU Ya; HU Ting (Cailiao gongcheng, 2021)
Layered double hydroxide (LDH) is an emerging material for corrosion protection of magnesium alloys. However, it is still controversial whether interlayer inorganic anions with strong affinity to LDH layers will exchange with corrosion anion Cl-. To solve this problem, three different inorganic anion intercalated MgAl-X-LDHs (X=PO43-, CO32-, and SO42-) were intended to synthesize and ion exchange experiments were carried out. The test results such as SEM and XRD show that PO43-, CO32-, and SO42- successfully enter the spaces among LDH layers to form three different anion intercalated MgAl-X-LDHs. The results of ion exchange experiments show that Cl- can exchange with the intercalated PO43- and CO32- anions in the LDHs when 10 g/L MgCl2 are added into the 3.5%NaCl (mass fraction) solutions, while the exchange process is hard when MgCl2 is not added into the solution. In the case of MgAl-SO42--LDH, regardless of whether the Mg2+ exists or not, the intercalated SO42- anions in the LDHs can be exchanged with high concentration Cl-, and cannot be exchanged with low concentration Cl-. These results provide theoretical guidance for the design and preparation of different types of LDH anticorrosive coatings on magnesium alloys.